The importance of employability skills to TVET and non-TVET graduates / Surina Nayan and Suhaimi Nayan - Nayan, Surina; Nayan, Suhaimi (Universiti Teknologi MARA, Perlis, 2024)
The paper focuses on employability skills, the differences between job and employability skills, the importance of employability skills for TVET and non-TVET graduates, the consequences of fresh graduates not having adequate skills to join the workforce, and employers’ expectations of fresh graduates. Twenty-one diploma students were involved in the study. Convenient sampling was used. A set of questionnaires with employability skills was distributed to respondents. The respondents were asked to rate their employability skills based on their importance. Descriptive statistics was used to analyze the data. The survey's findings show that communication skills are the most crucial employability skills, followed by self-management, problem-solving, organization, planning, learning, teamwork, leadership, and technology. Findings from the study are also in line with Yorke and Knight's employability theory, whereby graduates believe that a set of achievements, which includes skills, understandings, and personal attributes, will make them more likely to gain employment and be successful in their chosen careers. Thus, universities can assist students in becoming more employable by emphasizing developing their meta-cognitive skills, learning how to learn, and boosting their self-esteem.